Performance Analysis of a Free Space Optics Link with Multiple Transmitters/Receivers - Md Noor, Nur Haedzerin; Naji, Ahmed Wathik; Al-Khateeb, Wajdi (IIUM Engineering Journal, 2012)
ABSTRACT: Â Multiple transmitters/receivers (TX/RX) are used to improve the quality of Free Space Optics (FSO) communication systems. With the current needs of this technology for longer distance communication, the qualitative analysis of the system has become essential. In this work, the received power level (PR) and bit error rate (BER) are considered to influence the FSO link performance. The relationship between the two parameters are investigated and analysed. Furthermore, the received power for various numbers of TXs and RXs are experimentally measured and compared with the values obtained from theoretical calculations. The first part of the work deals with the theoretical calculation and simulation designs of multiple laser beams based on the commercial FSO used in actual sites. The second part describes the practical work and analysis of the systemâ€™s performance. ABSTRAK: Pemancar/penerima berganda (TX/RX) digunakan bagi meningkatkan kualiti sistem komunikasi Ruang Optik Bebas (FSO). Analisis kualitatif ke atas sistemnya adalah penting bagi keperluan semasa teknologi ini untuk jarak jauh. Di dalam kajian ini, aras kuasa penerima (PR) dan kadar ralat bit (BER) telah diambilkira bagi menentukan prestasi rangkaian FSO. Hubungan di antara kedua-dua parameter telah dikaji dan dianalisis. Seterusnya, kuasa penerima untuk pelbagai nombor TXs dan RXs diukur secara eksperimen dan dibandingkan dengan nilai teori yang dikira. Bahagian pertama skop kajian berkaitan dengan pengiraan teori dan rekabentuk simulasi sinaran laser berdasarkan FSO komersial di lapangan. Bahagian kedua kajian adalah kerja lapangan dan analisis prestasi sistem. KEY WORDS:Â Free Space Optics (FSO) link; Multiple TX/RX FSO; bit error rate (BER); eye diagram.